2020
DOI: 10.4067/s0718-58392020000300444
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bokashi improved with rock phosphate on parsley cultivation under organic greenhouse management

Abstract: The application of stabilized organic matter to the soil is essential for the sustainability of a production system. Bokashi is a biofertilizer produced by the aerobic decomposition of organic matter that contributes to the conservation of soil fertility. The objective of this study was to evaluate the effect of bokashi improved with rock phosphate on a curled parsley crop (Petroselinum crispum [Mill.] Fuss var. crispum) under organic management. The process to prepare bokashi at 9% rock phosphate (BP) and wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…In Paphiopedilum arminiacum, increase in nitrogen concentrations in fertigation increased the Clf A+B content (Zong-Min et al, 2012). Likewise, Maass, Céspedes and Cárdenas (2020) observed that the fertilization of Petroselinum crispum with the highest concentrations of bokashi increased shoot dry mass and chlorophyll content.…”
Section: Chlorophyll and Carotenoid Contentmentioning
confidence: 81%
“…In Paphiopedilum arminiacum, increase in nitrogen concentrations in fertigation increased the Clf A+B content (Zong-Min et al, 2012). Likewise, Maass, Céspedes and Cárdenas (2020) observed that the fertilization of Petroselinum crispum with the highest concentrations of bokashi increased shoot dry mass and chlorophyll content.…”
Section: Chlorophyll and Carotenoid Contentmentioning
confidence: 81%
“…The degradation of P content in coconut husks was strongly suspected if the P solubilizing bacteria positively correlates with the molasses added. The bacteria in EM4 have been shown to effectively dissolve P in raw materials (Maass et al, 2020). Moreover, the coconut husk is a K and P source and has good water solubility (Gbollie et al, 2021), so its addition is proven to increase the phosphorus content of liquid fertilizer.…”
Section: Resultsmentioning
confidence: 99%
“…The association of Bokashi with rock phosphate increases chlorophyll index and dry matter in parsley (Petroselinum crispum [Mill.] Fuss) (Maass et al, 2020). Penergetic-K and Penergetic-P activators are produced based on bentonite and molasses that are processed by a technology in which bentonite clays are subjected to the application of electric and magnetic fields (Artyszak & Gozdowski, 2020).…”
Section: Introductionmentioning
confidence: 99%